On web-applications usability testing - Boris M. Basok; Alena N. Rozhanskaya; Sergey L. Frenkel (Российский технологический журнал)
The paper discusses the task of organizing the usability testing of web applications that are in pilot or industrial operation. A usability testing technique is described that combines the development, debugging and execution of test scenarios, and analysis of the received test data. The development of test scenarios is based: on the use of the accumulated experience of users who have already worked with this application or with another, similar in functionality; on the use of web analytics, which can provide scenarios of the behavior of user data on the site; and on the use of statistical data on visits to specific pages. Simultaneously with this approach, a different approach is used in the construction of tests. It is based on the development of tests aimed at identifying defects in the program. Debugging and execution of test tasks is carried out in the same way as it is realized when performing functional testing of web applications using testing automation tools. In addition, the analysis of the data obtained during the operation using web analytics makes it possible to form a group of respondent testers, whose capabilities reflect the capabilities of the entire set of probable users of this web application. The approaches outlined in the work were put into practice. As an example, the article provides test data for the page of the admissions committee of MIREA – Russian Technological University – priem.mirea.ru. The obtained experimental data showed that, despite testing the usability of software at the development stages, some errors in the operation of web applications remain undetected. The cost of detecting and eliminating these errors increases significantly. Therefore, it is recommended in the work to increase the level of usability already in the early stages of development. In particular, for the operational prediction of the level of usability, it is desirable to have mathematical tools for modeling the behavior of the designed system and the user.